A justiça e o bem em John Rawls : um estudo da complementaridade do justo e do bem na justiça como equidade - Lessa, Jaderson Borges (2014)
The present work intends to analyze to what extent the concept of fairness and the ideas of the good complement the theory of justice of the most important political philosopher of the twentieth century. It is important to awake the key reading of complementarity in the debate about fairness and good on Justice as Fairness without sacrificing the important critical perspectives, even a little distant from the canon of prevailing interpretations as long as integrating with many others and compose more comprehensive criteria for interpretation. John Rawls is acknowledged as an author belonging to the liberal tradition, whose thinking seeks to ensure the priority of the right over the good, an indispensable task to defend individual liberty. Although respecting the diverse ideas of the good, liberalism rejects the possibility of fixing a particular doctrine of good for the whole society. Rawls has been widely studied over the past decades, but little was written his use of ideas of the good regarding justice in his political conception. To establish how is the relationship of ideas of the good and the idea of justice in his theory is the basis for understanding the author's attempt to reconcile the good and the justice on Theory of Justice as Fairness. This idea of complementarity that followed his whole theory of justice was part of the major changes in his work and it would be a mistake to forget such argument in the discussion of how a contemporary democratic society can be good and fair for its citizens. The importance of this argument is also revealed in Rawls' idea that the greater the lack of complementarity between the fair and the good, greater is the prospect of having instability in society along the evils that follow such inconsistency. The idea of complementarity between the good and the fair, in all its breadth, was present during the written of this author's major works. To enrich the critique on Rawls is the ultimate intent of submitting to an examination of what was used by him to design his work.